2016
DOI: 10.1371/journal.pone.0155012
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory and Compensatory Postural Adjustments in Response to External Lateral Shoulder Perturbations in Subjects with Parkinson’s Disease

Abstract: The purpose of this study was to investigate the anticipatory (APA) and compensatory (CPA) postural adjustments in individuals with Parkinson’s disease (PD) during lateral instability of posture. Twenty-six subjects (13 individuals with PD and 13 healthy matched controls) were exposed to predictable lateral postural perturbations. The electromyographic (EMG) activity of the lateral muscles and the displacement of the center of pressure (COP) were recorded during four time intervals that are typical for postura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Previously, Tai Chi training has been shown to improve postural control during standing [ 1 , 2 ] and walking [ 3 ], as well as the ability to recover balance after a slip [ 3 ]. The present study indicated that it could also offer an effective approach to counteract the deterioration of reactive postural control, which is seen in older adults [ 25 ] and patients with neuromuscular diseases [ 20 , 26 , 27 ]. Importantly, previous studies have already demonstrated that performing Tai Chi is safe and effective for Parkinson’s disease [ 6 ] and multiple sclerosis [ 28 ] patients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously, Tai Chi training has been shown to improve postural control during standing [ 1 , 2 ] and walking [ 3 ], as well as the ability to recover balance after a slip [ 3 ]. The present study indicated that it could also offer an effective approach to counteract the deterioration of reactive postural control, which is seen in older adults [ 25 ] and patients with neuromuscular diseases [ 20 , 26 , 27 ]. Importantly, previous studies have already demonstrated that performing Tai Chi is safe and effective for Parkinson’s disease [ 6 ] and multiple sclerosis [ 28 ] patients.…”
Section: Discussionmentioning
confidence: 90%
“…Because adaptations to stability training are highly task-specific [ 17 ], it could be expected that reactive postural responses to external perturbations at this level are improved with Tai Chi training. Applying sudden external perturbations (by suddenly applying or releasing a load) to the upper body has been also extensively used to study postural control [ 18 , 19 , 20 , 21 , 22 ]; however, to the best of our knowledge, no study to date has examined reactive postural responses to external upper body perturbations in Tai Chi practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more precisely calibrated truncal perturbations have been attempted in the laboratory with motors and pendulums (de Azevedo et al 2016; Di Giulio et al 2016). In contrast, motion tracking is a relatively simple technique (albeit still requiring specialized equipment), and this has been previously employed to assess the “push and release test” (an alternative to the more widely used pull test) (Jacobs et al 2006; Smith et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Platform translation involves intense “bottom up” perturbations, generating an initial lower limb response as occurs when slipping on a wet floor (Horak et al 1997). In contrast, the pull test employs a “top down” perturbation, with initial displacement and response of the trunk, as may occur when bumped in a crowd, and this generates a different pattern of motor recruitment (Colebatch et al 2016; de Azevedo et al 2016; Di Giulio et al 2016; Govender et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…APA is a pre-programmed action starting voluntarily (1,3) and reflect a feedforward control and the changes are seen in the background activity of muscles (29,62,63), it is related on previous experiences and learning of subject (64). APA are the changes in the activity of the postural muscles before postural disturbance self-generated, for example, before the rapid APA and CPA magnitude depends on direction and degree of postural disturbances classified as either internal (generated by forces and torques developed during the movement of subject) or external (produced by forces around the subject), but is not limited to this (64). It is known that the magnitude of APA depends on the direction and magnitude of disturbance and body stability.…”
Section: Vertical Position Is Inherently Unstable Because the Locatiomentioning
confidence: 99%